Influencing the Purchase Decisions on Luxury Fashion Brand: Social and Personal Value as the Influencers - Ian, Sebastian; Gunadi, Willy (Jurnal Manajemen, 2024)
The fashion industry is one of the world’s largest industries and holds an important part in consumer culture nowadays. This re- search objective is to find the impact of social value and personal value on purchase decisions on luxury fashion brand products. This research is based on Indonesian respondents who have purchased fashion luxury brand products at least once. The total respondent of this research is 203 respondents, which was gathered using online questionnaire. The data was processed using PLS-SEM analysis method to predict the relationship between variables. The finding of this research is product quality in personal value doesn’t affect customer purchase decisions towards luxury fashion brand products, while social value, perceived price, and brand image affect the customer purchase decisions.